IMPLEMENTASI TEKNOLOGI TEPAT GUNA PENGONTROL KEKERUHAN AIR UNTUK OPTIMALISASI AKUAKULTUR BUMDES: SEBUAH MODEL PEMBERDAYAAN KOLABORATIF KARANG TARUNA DAN BUMDES DI DESA PAKAPASAN GIRANG - Siskandar, Ridwan; Ekawati, Nurul; Kusumah, Billi Rifa; Pengestuti, Dheni Dwi; Ruspendi; Rizki, Muhamad; Cintia, Cicin; Usniyati; Mutmainah, Iin; Hadijaya, Maulana; Ali, Muhamad Sidiq; Molinda, Meutya; Kiswanto, Andi; Cipto, Lusia; Novanti, Teni; Wiyoto (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
This community service program implemented the HydroSense appropriate technology to address water turbidity issues in tilapia cultivation at BUMDes Pasir Gubah, Pakapasan Girang Village. Using a collaborative approach between the Youth Group (Karang Taruna) and BUMDes, the program included socialization, technical and managerial training, device installation, and mentoring. Monitoring results over three months showed significant impacts: fish mortality decreased by 82.3% (from 48% to 9.5%), biomass productivity increased by 43.2%, and income surged by 69% per pond due to improved fish quality enabling a higher selling price. The program not only resolved technical problems but also built an empowerment and sustainability model through strengthening local institutions.